Case report: The use of metagenomic next-generation sequencing to diagnose Lemierre’s syndrome caused by lost root canal fillings in a 33-year-old patient with metabolic syndrome - Zhou, Yimeng; Zhai, Yongzhen; Wang, Yan; Zhang, Dan; Feng, Guohe (Frontiers in Medicine, 2024)
Background Lemierre’s syndrome is a rare and serious complication of pharyngitis with an estimated annual incidence of 1 in 100,000 people worldwide. It is characterized by septic thrombophlebitis of the internal jugular vein with metastatic infection, usually after oropharyngeal infection. Rare cases of Lemierre’s syndrome have been reported to be caused by odontogenic infection. Case report A 33-year-old male visited our hospital with symptoms of fever and sore throat for 16 days. The other symptoms included pain in his left neck and shoulder. In addition, metabolic syndrome was diagnosed based on waist circumference, diabetes, and hyperlipidemia. Fusobacterium necrophorum bacteria was detected using the metagenomic next-generation sequencing (mNGS) technique. The enhanced computerized tomography (CT) scan showed thrombosis of the left proximal jugular vein and brachiocephalic vein. Based on these observations, Lemierre’s syndrome was diagnosed. The etiology was that the fillings in the root canal tooth were lost with no blood or pain about 2 weeks before the onset. The patient recovered after treatment with antibiotics and blood purification. Conclusion Lemierre’s syndrome should be evaluated for patients with fever, sore throat, and neck pain. If the loss of fillings from root canal therapy occurs, especially for those with metabolic syndrome, we should be aware of the possibility of this disease. Furthermore, the mNGS test can be used as a crucial supplementary diagnostic tool for patients with undetermined fever.